Changes in Oxidative Stress and Inflammatory Biomarkers in Fragile Adults over Fifty Years of Age and in Elderly People Exclusively Fed Enteral Nutrition. (1st December 2015) - Mesa, Maria D.; Olza, Josune; Gonzalez-Anton, Carolina; Aguilera, Concepcion M.; Moreno-Torres, Rosario; Jimenez, Africa; Perez de la Cruz, Antonio; Ruperez, Azahara I.; Gil, Angel
Abstract : We aim to evaluate whether exclusive feeding of an enteral formula enriched with n -3 long chain polyunsaturated fatty acids ( n -3 LC-PUFA) affects oxidative stress and the antioxidant defence system and may improve the levels of some relevant inflammatory, and cardiovascular biomarkers in frail adults over fifty years of age and in elderly subjects. Fifty-five patients were divided into two groups and were exclusively fed a newly designed normoproteic and isocaloric enteral formula enriched with eicosapentaenoic (98 mg/d) and docosahexaenoic acids (46 mg/d) (n = 26 ) or a reference enteral diet (n = 29 ). Oxidative, inflammatory and cardiovascular risk biomarkers and red blood cell fatty acid profiles were determined at the beginning and after 90 and 180 days of feeding. The n -3 LC-PUFA percentage tended to be higher (P = 0.053 ) in the experimental group than in the reference group. Administration of the n -3 LC-PUFA diet did not increase oxidative stress or modify plasma antioxidant capacity but decreased antioxidant enzymatic activities. MMP-9 plasma concentration decreased with both formulae, whereas tPAI-1 tended to decrease (P = 0.116 ) with the administration of the experimental formula. In conclusion, administration of the new n -3 LC-PUFA-enriched product for 6 months did not negatively alter the oxidative status and improved some cardiovascular risk biomarkers.